Exploring the importance of emotional quotient in construction : perspectives from health and safety professionals in South Africa - Smallwood, John; Emuze, Fidelis; Bloomberg, Charissa (Journal of Construction Project Management and Innovation, 2014)
Self-regard, emotional self-awareness, flexibility, problem solving, and stress tolerance, inter alia, constitute attributes that affect how well activities are carried out by individuals. Thus, construction activities that are people intensive require a measure of emotional quotient (EQ) to enhance project performance, especially with regard to health and safety (H&S). EQ is important due to: intrapersonal EQ; relationship with one self; interpersonal EQ; stress management; adaptability, and general mood of employees. The aforesaid in due course impact on performance related to the project parameters in the sector, inter alia, cost, H&S, time, quality, and productivity. The purpose of the paper is to present the findings of an exploratory study that was conducted to determine the perceived importance of EQ in terms of managing construction H&S and the extent to which EQ contributes to optimising H&S performance on projects in South Africa. This is aimed at contributing to the enhancement of H&S performance in construction.
Published Article
Keywords: Construction; Emotional Quotient; Health and Safety (H&S); Performance; Project; South Africa